Penilaian Tingkat Kesehatan Lembaga Perkreditan Desa Se-Kecamatan Denpasar Utara Tahun 2016-2017 - Wibawa, I Nyoman Putra; Putra Astika, Ida Bagus (E-Jurnal Akuntansi, 2020)
The LPD contribution in the North Denpasar can sustain the financial economy of the community, especially the poor in the North Denpasar. The purpose of this study was to determine the development of the level of financial health at the Village Credit Institution (LPD) of North Denpasar in 2016-2017 with CAMEL analysis. The number of samples used was 10 LPDs in North Denpasar with a nonprobability sampling. Data collected through observation and interviews. Data analysis technique used is  non-statistical quantitative approach. Based on the results, it was found that LPD in the North Denpasar in 2016-2017 with an average sample size of 10 LPDs were categorized as healthy, with CAMEL values above 80. The Ubung LPD for the year 2016-2017 obtained the highest CAMEL score of 99.60. The Kedua LPD in the period of 2016-2017 obtained the lowest CAMEL value, amounting to 81.45. Keywords: Capital; Asset; Management; Earnings; Liquidity.